Improvements in Efficiency and Selectivity for C–F Bond Halogen-Exchange Reactions by Using Boron Reagents - Ćorković, Andrej; Dorian, Andreas; Williams, Florence J. (Synlett, 2022)
The use of boron Lewis acids as instigators of bond cleavage offers a number of synthetic possibilities. A unique feature of this class of reagents is the ability to functionalize otherwise inert C–F bonds. We summarize notable developments in C–F bond halogen exchange using Lewis acidic boron reagents and we conclude by featuring our group’s advances in activating CF3 groups by using boron trihalides.1 Introduction2 Boron-Mediated Halogen Exchange3 Mono-Selective C–F Activation4 Conclusions
Keywords: halogen exchange; boron trihalides; C–F bond activation; trifluoromethyl group activation; C–F functionalization; Lewis acids